The production of in situ (Mo, Ti)(C, N)-based cermets without a core/rim structure by reaction hot pressing: Formation mechanism and mechanical properties. Issue 24 (15th December 2022) - Wang, Tianle; Zhao, Xianrui; Fang, Yihang; Zhang, Mengxian
Abstract: A novel reaction hot pressing process was developed for the fabrication of in situ (Mo, Ti)(C, N)-based cermets without a conventional core/rim structure. Moreover, the reaction mechanism of the Co–Mo–Ti–TiN–C system was investigated. The results indicate that the allotropic transformation of hexagonal ε Co→cubic α Co occurred first. Then, solid-state reactions of powder mixtures were conducted, which contributed to the synthesis of Mo2 C, CoTi2, and TiC. Continuous heating induced a peritectic reaction of CoTi2 →CoTi + Co–Ti liquid. The presence of a Co–Ti liquid facilitated the dissolution of C, and the production of a Co–Ti–C melt. In the liquid, TiC was prepared. Then, in situ TiC was combined with ex situ TiN to synthesise Ti(C, N). As the temperature increased, Mo/Mo2 C diffused into whole Ti(C, N) particles, resulting in the formation of micro coreless (Mo, Ti)(C, N) grains. Subsequently, residual Mo2 C and part of (Mo, Ti)(C, N) dissolved into a Co–Ti–C liquid, resulting in the formation of a Co–Mo–Ti–N–C melt. Once the liquid became saturated, ultrafine (Mo, Ti)(C, N) particulates with a weak or non-existent core/rim structure were precipitated. (Mo, Ti)(C, N)-based cermets can be prepared at 1523 K. An increased sintering temperature enhanced the relative density and homogeneity of the cermets, eliminated the by-products Mo2 C and Co3 Mo, and promoted the formation of more ultrafine (Mo, Ti)(C, N) particles. These effects increased the hardness and fracture toughness of the prepared cermets. The results of this work provide valuable guidance for the development of in situ coreless Ti(C, N)-based cermets.